2024
DOI: 10.3389/fgene.2024.1327216
|View full text |Cite
|
Sign up to set email alerts
|

Research on stem cell therapy for spinal cord injury: a bibliometric and visual analysis from 2018–2023

Ruxing Liu,
Bo Peng,
Jie Yuan
et al.

Abstract: Objectives: The aim of this study was to conduct a bibliometric analysis of the literature on stem cell treatment for spinal cord injury to gain an intuitive understanding of how the field is progressing, discover topics of interest, and determine what development trends are emerging in this field.Background: Spinal cord injury and its complications often cause an enormous economic burden, and postinjury repair and treatment have always been challenging in clinical and scientific research. Stem cell therapy fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Keywords are the condensed summary of an article, and if they frequently appear together, they are considered to be a research hotspot in this field (Liu et al, 2024;. The cooccurrence analysis of keywords in this study showed that bone marrow transplantation, enzyme replacement therapy, lysosomal storage disease, hurler syndrome, Children, alpha-l-iduronidase, hunter-syndrome, and central nervous system were the research hotspots in the field of MPS.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Keywords are the condensed summary of an article, and if they frequently appear together, they are considered to be a research hotspot in this field (Liu et al, 2024;. The cooccurrence analysis of keywords in this study showed that bone marrow transplantation, enzyme replacement therapy, lysosomal storage disease, hurler syndrome, Children, alpha-l-iduronidase, hunter-syndrome, and central nervous system were the research hotspots in the field of MPS.…”
Section: Discussionmentioning
confidence: 72%
“…Frontiers in Genetics frontiersin.org visualizes the number of publications, but also reflects their connections and the evolution and development of the field as a whole, and it can help us to retrieve resources more efficiently (Liu et al, 2024). Among the top 100 most cited articles, 27 are MPS I (11 of them on MPS IH), 11 are MPS II, nine are MPS III (four on MPS IIIA), five are MPS IV (all on MPS IVA), eight are MPS VI, three are MPS VII, one is MPS IX, and the rest of the articles do not have a clear classification of the types of MPS were not categorized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation